Antenatal urolithiasis: A case report - Bose, Sumona; Iyengar, Arpana; Shubha, Attibele Mahadevaiah (Frontiers in Pediatrics, 2022)
Introduction Although pediatric urolithiasis is an established entity, its antenatal diagnosis is rare. We hereby report a case detected at 20 weeks gestation and discuss the etiopathogenesis, predisposition, and surveillance following intervention. Case report A 2-year-old girl with left renal pelvic calculus detected antenatally at 20 weeks was evaluated. Left hydronephrosis, obstructive pelvic calculus with a decrease in differential renal function on ethylene dicysteine (EC) renogram was confirmed. The metabolic workup was normal. Following stone extraction by left pyelolithotomy, a left ureteropelvic junction obstruction secondary to a mucosal valve was apparent which was excised and left pyeloplasty was done. Stone analysis revealed 100% cystine. Differential renal function and drainage improved post-surgery. The child, however, did not have a follow-up in the interim and presented with a recurrent stone one and a half years later. Conclusion Knowledge of antenatal urolithiasis ensures continued follow-up, evaluation for metabolic disorders, and associated structural defects, especially with increasing stone size and increasing hydronephrosis. This helps in timely intervention and continued surveillance.